2021
DOI: 10.1182/blood-2021-148173
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cardiac Effects of Successful Non-Myeloablative HLA-Matched Sibling Transplants in Sickle Cell Disease

Abstract: INTRODUCTION Cardiopulmonary complications lead to early mortality in adults with sickle cell disease (SCD). We previously showed in a small single-center study that cardiac morphology improves by one year after successful non-myeloablative hematopoietic stem cell transplantation (HSCT). Since cardiac outcomes following HSCT are not well-described, we sought to extend our results to a larger group of SCD patients from the National Institutes of Health (NIH) and University of Illinois Chicago (UI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…35 Mean left ventricular ejection fraction in adults decreased from 65% and 61.5% to 60% and 59.8% in these two studies, 34,48 but cardiac size, mass and diastolic dysfunction improved. 48 Peak TRJV was assessed before and after HSCT in seven studies. 19,22,24,34,35,43,48 However, only the largest three studies reported mean TRJV for the whole cohort before and after HSCT, and could be included in the meta-analysis.…”
Section: Cardiac Functionmentioning
confidence: 71%
See 4 more Smart Citations
“…35 Mean left ventricular ejection fraction in adults decreased from 65% and 61.5% to 60% and 59.8% in these two studies, 34,48 but cardiac size, mass and diastolic dysfunction improved. 48 Peak TRJV was assessed before and after HSCT in seven studies. 19,22,24,34,35,43,48 However, only the largest three studies reported mean TRJV for the whole cohort before and after HSCT, and could be included in the meta-analysis.…”
Section: Cardiac Functionmentioning
confidence: 71%
“…There was no statistical difference in shortening fraction (SMD 0.24, p = .53), but left ventricular ejection fraction decreased following HSCT (SMD 0.53, p = <.01; Figure 2, Figure S2). The decrease in left ventricular ejection fraction was more pronounced in the two studies comprising adult patients, 34,48 compared to children. 35 Mean left ventricular ejection fraction in adults decreased from 65% and 61.5% to 60% and 59.8% in these two studies, 34,48 but cardiac size, mass and diastolic dysfunction improved.…”
Section: Cardiac Functionmentioning
confidence: 78%
See 3 more Smart Citations